THE ASSOCIATIONS OF SOCIAL ISOLATION WITH MEDICAL AND LONG-TERM CARE UTILIZATION AMONG OLDER ADULTS IN JAPAN. (16th November 2018) - Mitsutake, S; Koike, T; Ishizaki, T; Nishi, M; Kobayashi, E; Hasebe, M; Tamiya, N; Fujiwara, Y
Abstract: This study aimed to examine whether social isolation (isolation) defined as having less contact than once a week with anyone outside the household was associated with medical and long-term care utilization. We conducted a two-wave questionnaire survey among city residents aged over 65 years (Wave 1 in 2008 and Wave 2 in 2010) in Wako city, Japan. From health insurance claim data and long-term care data from 2008 to 2011, the present cohort study extracted data receiving medical and long-term care and the related expenses in the three-year period. Using a two-part model to identify the association of isolation with receiving medical and long-term care and the related expenses, we analyzed 1, 520 older adults. Approximately 29.6% of the participants were isolated. Using logistic regression-adjusted covariates (sex, age, educational level, resident status, household income, instrumental activities of daily living, depression symptoms, and the prevalence of cardiovascular disease, liver disease or other diseases), isolation was negatively associated with receiving medical outpatient care (adjusted odds ratio: 0.407, 95% confidence interval[95%CI]: 0.235 to 0.703). Moreover, in the generalized linear model for data with a gamma distribution with a log-link function, isolation was negatively associated with outpatient care expenses (adjusted risk ratio: 0.833, 95%CI: 0.747 to 0.928). There were no significant associations of isolation with inpatient care and long-term care and the related expenses. The negative associations of isolation with receiving outpatient care and the related expenses among older adults may demonstrate that those with isolation do not receive the medical outpatient care they required.